Managerial opportunistic behavior and firm value: Empirical study of manufacturing companies in Indonesia - Jeudi Agustina TP Sianturi; Sugeng Wahyudi; Irene Rini Demi Pangestuti; Mohamad Nur Utomo (Management Science Letters, 2020)
This paper aims to investigate the relationship between managerial opportunistic behavior and the value of manufacturing companies listed on the Indonesia Stock Exchange, using two different indicators of company value. The first indicator looks at the value of the company from a less than ideal size and other indicators view the value of the company from the ideal size. By using 320 observations, the results of this study found evidence that managerial opportunistic behavior that is proxied by free cash flow plays a role in influencing the overvalued equity proxied by market books. Likewise, free cash flow plays an important role on influencing Tobin q. This study also establishes an indirect relationship of free cash flow to overvalued equity and Tobin q which is mediated by dividend policy. Empirical results show that dividend policy mediates the effect of free cash flow on overvalued equity and also Tobin q partially.